Impact of CTLA-4 checkpoint antibodies on ligand binding and Transendocytosis - Williams, Cayman; Kennedy, Alan; Robinson, Maximillian A.; Lloyd, Christopher; Dovedi, Simon J.; Sansom, David M. (Frontiers in Immunology, 2022)
Anti-CTLA-4 antibodies have pioneered the field of tumour immunotherapy. However, despite impressive clinical response data, the mechanism by which anti-CTLA-4 antibodies work is still controversial. Two major checkpoint antibodies (ipilimumab and tremelimumab) have been trialled clinically. Both have high affinity binding to CTLA-4 and occupy the ligand binding site, however recently it has been suggested that in some settings such antibodies may not block ligand-CTLA-4 interactions (1). Here we evaluated blocking capabilities of these antibodies in a variety of settings using both soluble and cell bound target proteins. We found that when ligands (CD80 or CD86) were expressed on cells, soluble CTLA-4-Ig bound in line with affinity expectations and that this interaction was effectively disrupted by both ipilimumab and tremelimumab antibodies. Similarly, cellular CTLA-4 binding to soluble ligands was comparably prevented. We further tested the ability of these antibodies to block transendocytosis, whereby CTLA-4 captures ligands from target cells during a cognate cell-cell interaction. Once again ipilimumab and tremelimumab were similar in preventing removal of ligand by transendocytosis. Furthermore, even once transendocytosis was ongoing and cell contact was fully established, the addition of these antibodies could prevent further ligand transfer. Together these data indicate that the above checkpoint inhibitors performed in-line with predictions based on affinity and binding site data and are capable of blocking CTLA-4-ligand interactions in a wide range of settings tested.